2008
DOI: 10.1016/j.abb.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic mitochondrial transport of glutathione: Studies in isolated rat liver mitochondria and H4IIE rat hepatoma cells

Abstract: Glutathione (GSH) is transported into renal mitochondria by the dicarboxylate (DIC; Slc25a10) and 2-oxo-glutarate carriers (OGC; Slc25a11). To determine whether these carriers function similarly in liver mitochondria, we assessed the effect of competition with specific substrates or inhibitors on GSH uptake in isolated rat liver mitochondria. GSH uptake was uniphasic, independent of ATP hydrolysis, and exhibited K m and V max values of 4.08 mM and 3.06 nmol/ min per mg protein, respectively. Incubation with bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…Mitochondrial Vit E and coenzyme Q levels increased in T 3 -and GC-1-treated rats according to what previously found in hepatic tissue (Venditti et al 2009a), whereas GSH levels were not modified by treatments although the cytosolic levels decreased (Venditti et al 2009a). This result is consistent with the observation that, during oxidative stressinduced tissue GSH depletion, liver mitochondria conserve GSH level (Venditti et al 1999b) by transport systems located on the inner membrane (Zhong et al 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Mitochondrial Vit E and coenzyme Q levels increased in T 3 -and GC-1-treated rats according to what previously found in hepatic tissue (Venditti et al 2009a), whereas GSH levels were not modified by treatments although the cytosolic levels decreased (Venditti et al 2009a). This result is consistent with the observation that, during oxidative stressinduced tissue GSH depletion, liver mitochondria conserve GSH level (Venditti et al 1999b) by transport systems located on the inner membrane (Zhong et al 2008).…”
Section: Discussionsupporting
confidence: 81%
“…In line with this, a recent study showed that incubation of rat liver mitochondria with butylmalonate (a dicarboxylate carrier inhibitor) and phenylsuccinate (a 2-oxoglutarate carrier inhibitor) inhibited GSH uptake by 45-50%, suggesting that these two transporters are only partially responsible for GSH uptake in rat liver mitochondria (153). Moreover, in H4IIE cells, a rat hepatoma cell line, that were stably transfected with the cDNA for the 2-oxoglutarate carrier, exhibited increased uptake of GSH and 2-oxoglutarate and were protected from cytotoxicity induced by hydrogen peroxide, methyl vinyl ketone, or cisplatin, demonstrating the protective function of increased mitochondrial GSH transport and mGSH levels in the liver (153). Because 2-oxoglutarate is a dicarboxylate, it could share the dicarboxylate carrier for its mitochondrial entry; thus, the competition seen between 2-oxoglutarate and GSH does not discard the participation of dicarboxylate carrier in the transport of GSH in liver mitochondria (26).…”
Section: Mgsh Transportmentioning
confidence: 65%
“…Thus, we found significant sequence differences between rat kidney and liver OGC, 97 although the functional implications of these differences are not entirely clear. One thing that is clear, however, is that although both carriers are expressed in kidney and liver mitochondria, their relative contribution to mitochondrial GSH uptake differs in the 2 tissues.…”
Section: Transport Across Mim Determines Mitochondrial Gsh Pool and Cmentioning
confidence: 75%
“…Although the 2 carriers essentially account for virtually all of the detectable GSH uptake in renal cortical mitochondria, 19,66 function of at least 1 additional carrier must be invoked to account for the observable transport in rat liver mitochondria. 97 To directly demonstrate the toxicological role of mitochondrial GSH transport in renal cells, we used an immortalized cell line derived from normal rat proximal tubules (NRK-52E cells) as a convenient experimental model. 58 Overexpression of the cDNA for either the DIC 59 or the OGC 94 markedly increased mitochondrial GSH transport rates and provided significant protection from oxidant-induced cell death by apoptosis.…”
Section: Transport Across Mim Determines Mitochondrial Gsh Pool and Cmentioning
confidence: 99%